Nitrogen release and leachable organic matter decomposition of anaerobically digested biosolids with variable pre-treatments. (1st March 2020) - Fischer, Sarah; McCarty, Greg; Ramirez, Mark; Torrents, Alba
Graphical abstract: Highlights: Fluorescence maxima >Ex: 400 unique to anaerobically digested (AD) leachates. Peak picking/ratio analysis more targeted than Fluorescence Regional Integration. Similar N releases for AD solids with variable pretreatments during soil incubation. Fluorescence >Ex: 400 of leachable organic matter decayed during incubations. Targeted organic matter characterization informs biosolids management programs. Abstract: Thermal hydrolysis pretreatments (THP) coupled to anaerobic digestion (AD) are implemented to treat municipal solids, but limited study indicates whether THP-AD materials merit different land application rates than AD biosolids without THP. Three AD biosolids types with either no pretreatment, THP, or two-hour fermentation were evaluated for differences in leachable dissolved organic matter (DOM), DOM decomposition, and nitrogen (N) releases in biosolids incubated in sandy loam soil. DOM characterizations of size exclusion chromatography, FTIR, and fluorescence maxima > Ex: 400 nm indicated similarities in among AD-DOM that contrasted waste activated sludge Milorganite and Suwannee River Organic Matter (SRNOM). Fluorescence peak picking was a more adaptable analysis for shifted leachate spectra than fluorescence regional integration (FRI). Peak ratio analysis is recommended over FRI for biosolids-DOM. The 3-month net inorganic N produced in biosolids-soil incubations was 155 ± 12.1, 149 ± 18.2, 140 ± 17.4, and 354 ± 15.1 mg N/kg for AD biosolids with no pretreatment, fermentation-AD, THP-AD, and Milorganite respectively. Overall, there was limited evidence of differences in leachable organic matter quality or net mineral N release after 105 days for AD solids with or without THP. Red-shifted fluorescence of leachates decayed by day 45 in aerobic biosolids-soil incubations, suggesting that larger, complex carbon sources liberated during solids stabilization may decompose readily in soils. Overall, other variables (source material, AD operation) may have a greater influence on final nutrient releases and organic matter quality than full-scale pretreatments to AD alone. Critical and targeted application of DOM spectroscopy specific to biosolid-leachates will improve use in advanced stabilization studies.